2018
DOI: 10.1021/acs.jchemed.8b00357
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Application of Cyclodextrin Metal–Organic Frameworks in an Undergraduate Teaching Laboratory

Abstract: Reported herein is a multidisciplinary laboratory experiment for advanced undergraduate students that includes elements of material synthesis, in the synthesis of cyclodextrin-containing metal−organic frameworks (CD-MOFs), and environmental chemistry, in the use of these MOFs for pollutant removal. This multiday laboratory experiment starts with the synthesis of cyclodextrin-containing metal−organic frameworks (CD-MOFs) using vapor diffusion crystal growth procedures, followed by the use of the CD-MOFs for a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 50 publications
0
19
0
1
Order By: Relevance
“…MOFs possess unique properties, including large surface areas, long-range crystallinity, tunability, and high porosity lending them to an exciting prospect that could be very beneficial to society, if realized at a large scale . Considering all the possible applications for MOFs that include wastewater decontamination, catalysis, chemical sensing, gas storage, and separation. The first step before the materials can be widely used in any technology is to find a way toward high-quality large-scale synthesis . With MOFs, however, cost and quality challenges which arise with upscaled synthesis hinder their successful realization .…”
Section: Introductionmentioning
confidence: 99%
“…MOFs possess unique properties, including large surface areas, long-range crystallinity, tunability, and high porosity lending them to an exciting prospect that could be very beneficial to society, if realized at a large scale . Considering all the possible applications for MOFs that include wastewater decontamination, catalysis, chemical sensing, gas storage, and separation. The first step before the materials can be widely used in any technology is to find a way toward high-quality large-scale synthesis . With MOFs, however, cost and quality challenges which arise with upscaled synthesis hinder their successful realization .…”
Section: Introductionmentioning
confidence: 99%
“…More broadly, these structures are defined as a highly porous three-dimensional network of metal cations connected by organic ligands (Furukawa et al, 2013). Applications of MOFs are extensively reported in the literature, and include environmental remediation via pollutant binding inside the MOF structure (Ejeromedoghene et al, 2020); supramolecular catalysis by encapsulating reactants (Ghasemzadeh et al, 2020); controlled crystallization via topological effects of MOF incorporation (Wang et al, 2020i), and a variety of other applications (Jones et al, 2018;Ding et al, 2020;Heo et al, 2020).…”
Section: Metal-organic Framework Pesticide Detectionmentioning
confidence: 99%
“…Crane et al proposed that structural changes of MOFs could be monitored with PXRD, and Wriedt et al presented the CO 2 capture performance of an ultrastable MOF, PCN-200 (PCN = porous coordination network) . Subsequently, Smith et al reported the reversible adsorption of CO 2 within CD-MOFs (cyclodextrin-based metal–organic frameworks), and Jones et al explored the potential of CD-MOFs for the removal of methylene blue from solution . Lyle et al introduced the concept of postsynthetic modification by changing amine groups on IRMOF-3 (isoreticular metal–organic framework-3) into amide groups and explored a series of MOF-808 samples as superacid catalysts .…”
Section: Introductionmentioning
confidence: 99%
“…10 Subsequently, Smith et al reported the reversible adsorption of CO 2 within CD-MOFs (cyclodextrin-based metal−organic frameworks), 11 and Jones et al explored the potential of CD-MOFs for the removal of methylene blue from solution. 12 Lyle et al introduced the concept of postsynthetic modification by changing amine groups on IRMOF-3 (isoreticular metal−organic framework-3) into amide groups and explored a series of MOF-808 samples as superacid catalysts. 13 Liu et al proposed an ultrasonicassisted method for the synthesis of HKUST-1 (HKUST = Hong Kong University of Science and Technology) with a highlight on green and sustainable chemistry.…”
Section: ■ Introductionmentioning
confidence: 99%